2014
DOI: 10.1007/s11606-014-3007-6
|View full text |Cite
|
Sign up to set email alerts
|

Use of Hospitalists and Office-Based Primary Care Physicians’ Productivity

Abstract: BACKGROUND: Growth in the care of hospitalized patients by hospitalists has the potential to increase the productivity of office-based primary care physicians (PCPs) by allowing them to focus on outpatient practice. OBJECTIVE: Our aim was to examine the association between utilization of hospitalists and the productivity of office-based PCPs. DESIGN/PARTICIPANTS: The cross-sectional study was conducted using the 2008 Health Tracking Physician Survey Restricted Use File linked to the Area Resource File. We anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…Whereas it has been demonstrated in the literature that the use of mid-level practitioners enhances physician productivity, Park & Jones (2015) found that the increased use of hospitalists (physicians who solely work with inpatients), there was an increase in primary care providers' surgery-visit productivity by approximately 10%. This increase in surgery visits also translated to fewer hospital visits, primarily due to higher quality primary care.…”
Section: Literature Reviewmentioning
confidence: 86%
“…Whereas it has been demonstrated in the literature that the use of mid-level practitioners enhances physician productivity, Park & Jones (2015) found that the increased use of hospitalists (physicians who solely work with inpatients), there was an increase in primary care providers' surgery-visit productivity by approximately 10%. This increase in surgery visits also translated to fewer hospital visits, primarily due to higher quality primary care.…”
Section: Literature Reviewmentioning
confidence: 86%
“…Whereas it has been demonstrated in the literature that the use of mid-level practitioners enhances physician productivity, Park and Jones [9] found that in the increased use of hospitalists (physicians who solely work with inpatients), there was an increase in primary care providers' surgery-visit productivity by approximately 10%. This increase in surgery visits also translated to fewer hospital visits, primarily due to higher quality primary care.…”
Section: Literature Reviewmentioning
confidence: 92%
“…Having more hospitalists reduces the amount of primary care physician time required for hospital rounds, freeing up time to see more patients in ambulatory settings; the increase in primary care productivity might not offset the loss of primary care providers to the hospitalist workforce, however. 23,24 Hospitals will not hire more hospitalists than are needed. Hence, as with many relatively young professions, a shift has been taking place that is not being captured by the workforce simulation model.…”
Section: Primary Care-trained Hospitalistsmentioning
confidence: 99%